Contextualized practices in arts education : an international dialogue on Singapore (Education Innovation Series,, 2013)
This edited book not only makes a much-needed contribution to research in arts education but also provides a strong grounding of evidential support for Singapore arts education, in contrast to the current state of affairs in arts education in many parts of the world where severe cuts in funding, lackluster support for the arts and imperialist agendas are pervasive. The case of and for Singapore - presented in this edited book through rich descriptions of the dedicated, contextualized practices of arts educators, artists and researchers - offers readers many valuable lessons and reflections on the continued survival and advancement of arts education.